2008
DOI: 10.1038/sj.bjc.6604363
|View full text |Cite
|
Sign up to set email alerts
|

Expression of SDF-1α and nuclear CXCR4 predicts lymph node metastasis in colorectal cancer

Abstract: Although stromal cell-derived factor (SDF)-1a and its receptor CXCR4 are experimentally suggested to be involved in tumorigenicity, the clinicopathological significance of their expression in human disease is not fully understood. We examined SDF-1a and CXCR4 expression in colorectal cancers (CRCs) and their related lymph nodes (LNs), and investigated its relationship to clinicopathological features. Specimens of 60 primary CRCs and 27 related LNs were examined immunohistochemically for not only positivity but… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
104
2

Year Published

2008
2008
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 131 publications
(114 citation statements)
references
References 29 publications
7
104
2
Order By: Relevance
“…A second mechanism that links visfatin to increased cancer risk is its role in enhancing cancer cell survival. Specifically, CRC cells express chemokine receptors, CXCR4 and CXCR7, both of which can bind SDF-1 that promotes survival and migration of the cancerous cells [101,102]. Wen-Shih Huang et al [96] demonstrated that increased production of visfatin leads to increased expression of SDF-1.…”
Section: Visfatinmentioning
confidence: 99%
“…A second mechanism that links visfatin to increased cancer risk is its role in enhancing cancer cell survival. Specifically, CRC cells express chemokine receptors, CXCR4 and CXCR7, both of which can bind SDF-1 that promotes survival and migration of the cancerous cells [101,102]. Wen-Shih Huang et al [96] demonstrated that increased production of visfatin leads to increased expression of SDF-1.…”
Section: Visfatinmentioning
confidence: 99%
“…SW403 cells were pretreated with or without STAT3-siRNA or 20 mM PD 98059, followed by stimulation with IL-22 (10 ng/ml) for 30 min, and nuclear protein was extracted as previously described. 28 EMSA was carried out with a Gel Shift Assay System (Promega) in accordance with the manufacturer's recommendation. Briefly, the probes were generated by 5 0 -end labeling with [g-32 P]ATP (Amersham Biosciences) and T4 polynucleotide kinase (Promega).…”
Section: Promoter Assaymentioning
confidence: 99%
“…HGF/Met couple is important for the cross-talk between metastasis and microenvironment [2], and its activation by hypoxia might be hypothesized based on data from normal and neoplastic cell types [19,20]. CXCR4 may drive tumor cells to the secondary sites (lymph nodes, bones) where CXCL12 specific ligand is produced [21], but the experimental data on human metastases are still preliminary [22,23]. Moreover, HIF-1α correlates with Met and metastasis in node-negative breast cancer [24,25].…”
mentioning
confidence: 99%